Influence Of Corporate Culture On The Choice Of Management Technologies At Industrial Enterprises (Open Herald: Periodical of Methodical Research, 2025)
This article analyzes the influence of corporate culture on the choice of management technologies at industrial enterprises within the framework of theoretical and methodological foundations. The essence of the concept of corporate culture, its structural elements, stages of development, principles, and its relationship with management technologies are explained. Modern methodological approaches to assessing corporate culture, as well as mechanisms for creating an effective management system through it, are considered on a scientific basis.